Etiology and clinical pattern of liver diseases in children - Salih, Maher M.; Ibraheem, Mohammad F.; Nader, Kefah E. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: liver diseases may not be recognized by clinicians, who can lead to a subsequent delayin the initiation of effective therapies, the commonest presenting signs and symptoms of pediatric liverdiseases include hepatomegaly, jaundice, coagulopathy or elevation of the liver enzymes or wasteproducts as ammonia.Objectives: To highlight the etiologies, pattern of presentations and the route of diagnosis of all liverdiseases in children less than 10 years referred to the Gastroenterology and Hepatology Unit inChildren Welfare Teaching Hospital over a six months period.Patients and methods: A prospective study was conducted in the Gastroenterology and HepatologyUnit in the Children Welfare Teaching Hospital / Baghdad Medical City hospital during the periodfrom first of December 2016 to the end of thirty first of May 2017.Forty patients aged below 10 years were thoroughly assessed for possible causes of liver disease andthe severity of liver damage. These patients were subjected to a detailed history, thorough physicalexamination and a list of investigationsResults: forty patients their age less than 10 years, the most common age group in this study was from1 year to 5 years was 17(40%), males are more affected than females in the ratio of 1.5:1, it was foundthat the mean age of onset is the biliary atresia and Galactosemia cases were within the first week oflife, congenital infection cases presented earlier than the two above groups. In this study most of thecases were diagnosed clinically and by available investigations and only cases of biliary atresia andglycogen storage diseases were diagnosed by liver biopsy.Conclusion: All patients presented late with complications, biliary atresia cases were very late inpresentation, all with fibrosis. Family history usually very important in hereditary liver diseases asgalactosemia and glycogen storage disease a careful physical examination in addition to previousmedical history most of the time gives a clue to the final diagnosis.